Source/sink interactions underpin crop yield: the case for trehalose 6-phosphate/SnRK1 in improvement of wheat - Lawlor, David W.; Paul, Matthew J. (Frontiers in Plant Science, 2014)
Considerable interest has been evoked by the analysis of the regulatory pathway in carbohydrate metabolism and cell growth involving trehalose (TRE). TRE is at small concentrations in mesophytes such as Triticum aestivum. Studies of TRE metabolism, and genetic modification of it, have shown a very wide and important role of the pathway in regulation of many processes in development, growth and photosynthesis. It has now been established that trehalose 6-phosphate (T6P), is formed from glucose-6-phosphate and UDP-glucose, derived from sucrose, by the action of trehalose phosphate synthase (TPS ) and broken down by trehalose-6-phosphate phosphatase (TPP) providing for subtle regulation. The concentration of T6P increases with sucrose concentration. Many of the effects of T6P on metabolism and growth occur via the interaction of T6P with the SnRK1 protein kinase system. A large concentration of sucrose increases T6P and thereby inhibits SnRK1, so stimulating growth of cells and their metabolism. The T6P/SnRK1 mechanism offers an important new view of how the distribution of assimilates to organs, such as developing cereal grains, is achieved. Changing T6P concentrations by genetically modifying TPS and TPP has altered photosynthesis, sugar metabolism, growth and development which affect responses to, and recovery from, environmental factors. This review briefly summarizes the factors determining, and limiting, yield of wheat, particularly mass/grain which is highly conserved. The interactions between the source and sink relations are addressed together with how T6P/SnRK1 might function to determine grain number, size, and yield. The possibility of how these might be increased by modifying trehalose metabolism is considered. Cereal yields globally are not increasing and careful targeting of T6P may offer a way of optimizing grain growth and thus increasing yield in wheat.